Strategi Menumbuhkan Motivasi Belajar PAI di Kalangan Siswa MAN 2 Tuban - Laili Nur Affida; Ali Mudlofir (Universitas Muhammadiyah Jember, 2021)
The world is shocked by the spread of the Covid-19 virus that has major impacts in nearly all fields, including in the field of education in Indonesia. One of the efforts to minimize the spread of the COVID-19 virus in the education sector is to conduct distance learning which is carried out using various types of platforms and media to support the learning process. The purpose of this study is to review the teacher's strategy in growing students' learning motivation. This research method is a descriptive qualitative research method. Data collection techniques used are observation and interview techniques. The results of this study are that the teacher uses a flipped classroom learning model strategy assisted by madrasa e-learning media made by the teacher himself. It is proven to be able to grow the learning motivation of students in Class X IPS 1 MAN 2 Tuban, so that it can have an impact on increasing student learning outcomes and goals of a learning can be achieved.